Strain-rate-driven shear mechanisms in additively manufactured CoCrFeMnNi chemically complex alloys - Shanshan Liu; Menglei Hu; Yuquan Meng; Lijun Xiao; Weidong Song (Journal of Materials Research and Technology)
The single-phase face-centered cubic (FCC) CoCrFeMnNi chemically complex alloy (CCA) was fabricated by selective laser melting (SLM), and the forced shear characteristics were investigated under quasi-static and dynamic loading using hat-shaped specimens with displacement confined by stopper rings. The SLM-printed CCA exhibits excellent shear resistance, with dynamic shear yield and peak strengths reaching ∼320 MPa and ∼661 MPa, respectively, and a maximum shear strain of ∼5.0. A pronounced strain rate sensitivity was observed, as evidenced by the formation of narrow adiabatic shear bands (ASBs, ∼30 μm in width) under high-strain-rate loading, in contrast to much broader shear localization zones (∼150–180 μm) under quasi-static conditions. The localized temperature rise within ASBs promoted rotational dynamic recrystallization (RDRX), resulting in the formation of ultrafine equiaxed grains and a significant reduction in dislocation density and subgrain boundaries. The structural stability and superior shear localization resistance of the SLM-printed CCA under dynamic conditions demonstrate its potential for high-rate impact or ballistic-resistant applications.